2019
DOI: 10.1088/1752-7163/ab0167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different exhaled nitric oxide analyzers in chronic respiratory disorders

Abstract: Background: Fractional exhaled nitric oxide (FeNO) measurement is a simple and non‐invasive method for monitoring eosinophilic airway inflammation. New portable analyzers for FeNO measurements are constantly being developed. The aim of our study was to evaluate the agreement of FeNO values measured by new portable analyzers. Materials and methods: FeNO was measured in 20 healthy subjects, 20 asthmatic and 20 chronic obstructive pulmonary disease patients using the analyzers Niox-VERO, Vivatmo-PRO and HypAir-Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…While we saw a preferential response to L-citrulline-induced lung function changes in FEV 1 among female participants with late-onset asthma, the lack of effect on other subgroups could be secondary to a type II error from having smaller number of study subjects. There is a possibility of bias in the results owing to the regression to the mean effect, since subjects measured for a second visit were screened by their FeNO value in the first visit (37,38). However, the potential for this bias is small, given that usually there is a high within-subject correlation of FeNO measurements (39).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…While we saw a preferential response to L-citrulline-induced lung function changes in FEV 1 among female participants with late-onset asthma, the lack of effect on other subgroups could be secondary to a type II error from having smaller number of study subjects. There is a possibility of bias in the results owing to the regression to the mean effect, since subjects measured for a second visit were screened by their FeNO value in the first visit (37,38). However, the potential for this bias is small, given that usually there is a high within-subject correlation of FeNO measurements (39).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…In recent years, FeNO has become a useful and non-invasive method to identify chronic inflammation of airway diseases [ 43 ], thus being successfully used to monitor adherence to steroid treatment in asthmatic patients [ 44 ]. Considering that steroids are able to reduce eosinophilic inflammation documented in most asthma phenotypes, FeNO is the perfect biomarker for monitoring steroid response in this clinical setting [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Vivatmo-PRO device is a portable device with an infrared sensor, which gives a rapid response and may not require storage of the sample in a chamber. In a recent study it has been showed a good correlation among some of these devices although the absolute exhaled NO measurements may differ to a clinically relevant extent [36]. Table 1 summarizes the performance characteristics of the most representative FE NO analysers.…”
Section: Assessment Of Fe Nomentioning
confidence: 99%